PROTON-BINDING STUDY OF STANDARD AND REFERENCE FULVIC ACIDS, HUMIC ACIDS, AND NATURAL ORGANIC MATTER - Ritchie J.D.; Perdue E.M. (My University, 2003)
The acid-base properties of 14 standard and reference materials from the International Humic Substances Society (IHSS) were investigated by potentiometric titration. Titrations were conducted in 0.1 M NaCl under a nitrogen atmosphere, averaging 30 min from start to finish. Concentrations of carboxyl groups and phenolic groups were estimated directly from titration curves. Titration data were also fit to a modified Henderson-Hasselbalch model for two classes of proton-binding sites to obtain ''best fit'' parameters that describe proton-binding curves for the samples. The model was chosen for its simplicity, its ease of implementation in computer spreadsheets, and its excellent ability to describe the shapes of the titration curves. The carboxyl contents of the IHSS samples are in the general order: terrestrial fulvic acids > aquatic fulvic acids > Suwannee River natural organic matter (NOM) > aquatic humic acids > terrestrial humic acids. Overall, fulvic acids and humic acids have similar phenolic contents; however, all of the aquatically derived samples have higher phenolic contents than the terrestrially derived samples. The acid-base properties of reference Suwannee River NOM are surprisingly similar to those of standard Suwannee River humic acid. Results from titrations in this study were compared with other published results from both direct and indirect titrations. Typically, carboxyl contents for the IHSS samples were in agreement with the results from both methods of titration. Phenolic contents for the IHSS samples were comparable to those determined by direct titrations, but were significantly less than estimates of phenolic content that were based on indirect titrations with Ba(OH)2 and Ca(OAc)2. The average phenolic-to-carboxylic ratio of the IHSS samples is approximately 1:4. Models that assume a 1:2 ratio of phenolic-to-carboxylic groups may overestimate the relative contribution of phenolic groups to the acid-base chemistry of humic substances.